(untitled) (Fiep Bulletin - online, 2014)
Talk about Brazil is mentioning its soccer. Every year several players show their talent in various Brazilian teams and are exported to other countries. Some of these players, because of their performance are considered more than just athletes, they become idols. One of them is Neymar, who was consecrated at Santos Soccer Club and negotiated by European team. During the negotiations, the media created narratives to show his potential as a player and justify his pass. Thus, this paper discusses the narrative strategies used by G1.globo.com to highlight the sporting performance of the player Neymar in the Confederations Cup and relate it to the European play style during the player’s transfer to Barcelona. We analyzed ten (10) headlines related to the period of announcement of the hiring of the player by Catalans and the end of the competition in Brazil. After analyzing the material, it was possible to identify several narrative strategies used by website highlighting the performance of Neymar in the Confederations Cup as the responsible for the good results obtained by the Brazilian national team; the association drawn between the athlete and a ’social responsible image’, as well as that of a person willing to share victory with colleagues, and even his ability on the field pointing to an athlete that is prepared to make his way in the European soccer. This indicates that the website uses specific strategies to associate the athletic performance of Neymar, reinforcing its potential for Brazilian sports idol, ready to shine in a Europe.